A hybrid process based-empirical approach to identify the association between wheat productivity and climate in the North China Plain during the past 50 years. (October 2018) - Zhu, Ruirui; Zheng, Hongxing; Wang, Enli; Jakeman, Anthony J.
Abstract: China is anticipated to face reductions in crop yield due to climate change. Combining a process-based agricultural model (APSIM) with a simplified empirical model, we investigate the association between wheat productivity and climate variables in the North China Plain (NCP) over the period 1960–2010. The results show that the spatial distribution of wheat productivity across NCP is negatively related to daily maximum temperature but positively to daily minimum temperature, solar radiation and precipitation. For most parts of the NCP, partial correlation analysis based on the APSIM simulation outputs indicates that the increasing daily minimum temperature could lead to higher productivity but the effects are counteracted by increases in daily maximum temperature. In the drier northern NCP, wheat productivity is largely discounted due to decreases in precipitation, while in the humid southern edge of the NCP, the productivity stimulation effect of warming is offset by dimming. Highlights: Process based agricultural model is used to simulate winter wheat productivity. Increasing daily minimum temperature improves yield but the effect is discounted by increase in daily maximum temperature. Increasing daily minimum temperature improves yield but the effect is counteracted by increase in daily maximum temperature. Wheat productivity is largely discounted by decreasing precipitation in the drier northern NCP. Productivity stimulation effect of warming is offset by dimming in the southern edge of NCP.